IMPLEMENTATION OF DIVERGENT THINKING IN EXPLORATION OF STUDENTS' CREATIVE EFFORTS IN READING HISTORICAL SOURCES FROM THE INTERNET - Firmansyah, Haris; Kusnoto, Yuver; Superman, Superman; Atmaja, Thomy Sastra (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2023)
In the digital era, learning history is more directed at reviving students' divergent thinking power. By applying this different way of thinking, teachers can use historical resources available on the internet. This research uses a Systematic Literature Review (SLR) to examine the idea of divergent thinking in exploring students' creative efforts in reading historical sources from the internet. Based on the results of the concept of developing different ways of thinking about historical sources, this is a form of student creativity to imagine the work of historians in using and evaluating historical sources to write history. Students can already see how ideas, especially initial ideas, that students share with historical sources shared by the teacher can lead to creative actions. And these results can be used as a benchmark for teachers on how to teach history based on the level of thinking ability and the way students learn. Abstrak: Pada era digital, pembelajaran sejarah lebih diarahkan untuk menghidupkan daya berpikir divergen siswa. Penerapan Cara berpikir berbeda ini guru dapat menggunakan sumber sejarah yang tersedia di internet. Penelitian ini menggunakan Systematic Literature Review (SLR), untuk mengkaji gagasan divirgen thinking eksplorasi usaha kreatif siswa dalam membaca sumber sejarah dari internet. Berdasarkan hasil konsep pengembangan cara berpikir yang berbeda dalam sumber sejarah ini adalah sebagai bentuk kreativitas siswa dalam rangka membayangkan karya sejarawan dalam menggunakan dan menilai sumber sejarah untuk keperluan penulisan sejarah. Siswa sudah dapat menampilkan bagaimana gagasan, gagasan awal yang siswa ceritakan dengan sumber sejarah yang dibagikan oleh guru sebagai tindakan kreatif. Dan hasil tersebut dapat dijadikan sebagai tolak ukur dari guru bagaimana seharusnya mengajar sejarah yang sesuai dengan tingkat kemampuan berpikir dan cara siswa belajar.